PENGEMBANGAN MUJARAB (MU’JAM JAWA-ARAB) SEBAGAI PENUNJANG KETERAMPILAN BERBICARA BAHASA ARAB SISWA SMA DI PATI - Inarotud Dujja; Nailur Rahmawati (Universitas Negeri Semarang, 2023)
Mujarab (Javanese-Arabic Dictionary) is a website-based online thematic dictionaryused to support the Arabic speaking skills of Senior High School students.This research was motivated by problems in Senior High School students inPati who still have difficulty in learning Arabic, especially in speaking skills. Thisdifficulty is caused by the lack of vocabulary mastered by students. One of the mediathat can be used to increase student vocabulary is a dictionary. Then researchersdeveloped a website-based online thematic dictionary called